Pengembangan Model Pengukuran Kesiapan Industri 4.0 Untuk Perusahaan Manufaktur di Indonesia - Hauw Sen Rimo Tan; Aditya Andhika; Francisca Dini Ariyanti; Khristian Edi Nugroho Soebandrija (Universitas Mercu Buana, 2019)
Nowadays, manufacturing companies in Indonesia are facing a great challenge in Industry 4.0 era. Manufacturing companies perceive Industry 4.0 is complex and could disturb their business process with uncertainty in results by implementing it. In other side, manufacturing companies also have difficulty in assessing their readiness to start Industry 4.0 transformation process and fail to prepare strategies and action plans clearly. This research developed a measurement model of Industry 4.0 readiness with 2 aspects, 5 dimensions and 20 variables that could be used by manufacturing companies to asses their current state. The dimensions “Awareness” and “Leadership and Strategy” are used to measure company readiness in “Knowledge” aspect, while the dimensions “People and Culture”, “Technology” and “Operation” are used to measure company readiness in “Resources Capability” aspect. The result of the measurement categories the company in 4 level of readiness, i.e.: “Not Ready”, “Conditional Ready”, “Basic Readiness” and “Fully Ready”. This model has been tested and used to measure Industry 4.0 readiness for an electronic manufacturing company located in Jabodetabek and showed that the model is easy and practical to be used in a real manufacturing company. Keywords: Industry 4.0, readiness measurement, readiness model, readiness index